Environmental conditions associated with carbonate-bearing rocks in lower Hawksbill Gap, Jezero western fan, Mars - Rebecca M.E. Williams; Joel A. Hurowitz; Linda C. Kah; Gwénaël Caravaca; Sanjeev Gupta; Nicolas Mangold; Michelle E. Minitti; R. Aileen Yingst; Kyle Uckert; Roger C. Wiens; Michael Tice; Megan Kennedy Wu; et al. (Icarus, 2026)

10 keV electron irradiation of methane ices at ocean world surface temperatures - Michael S. Bramble; Kevin P. Hand (Icarus, 2024)

Topography formation driven by sublimation of pure species on icy airless worlds - Antonio Macias Canizares; Daniel F. Berisford; David Goldstein; Philip Varghese; Laurence Trafton; Jordan Steckloff; Kevin P. Hand (Icarus, 2024)

Hot Vents Beneath an Icy Ocean: The Aurora Vent Field, Gakkel Ridge, Revealed - Eva Ramirez-Llodra; Claudio Argentino; Maria Baker; Antje Boetius; Carolina Costa; Håkon Dahle; Emily Denny; Pierre-Antoine Dessandier; Mari Eilertsen; Benedicte Ferre; Christopher German; Kevin Hand; et al. (Oceanography, 2023)
Evidence of hydrothermal venting on the ultra-slow spreading Gakkel Ridge in the Central Arctic Ocean has been available since 2001, with first visual evidence of black smokers on the Aurora Vent Field obtained in 2014. But it was not until 2021 that the first ever remotely operated vehicle (ROV) dives to hydrothermal vents under permanent ice cover in the Arctic were conducted, enabling the collection of vent fluids, rocks, microbes, and fauna. In this paper, we present the methods employed for deep-sea ROV operations under drifting ice. We also provide the first description of the Aurora Vent Field, which includes three actively venting black smokers and diffuse flow on the Aurora mound at ~3,888 m depth on the southern part of the Gakkel Ridge (82.5°N). The biological communities are dominated by a new species of cocculinid limpet, two small gastropods, and a melitid amphipod. The ongoing analyses of Aurora Vent Field samples will contribute to positioning the Gakkel Ridge hydrothermal vents in the global biogeographic puzzle of hydrothermal vents.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Ocean System Science to Inform the Exploration of Ocean Worlds - Christopher German; Donna Blackman; Andrew Fisher; Peter Girguis; Kevin Hand; Tori Hoehler; Julie Huber; John Marshall; Kathryn Pietro; Jeffrey Seewald; Everett Shock; Christophe Sotin; et al. (Oceanography, 2022)
Ocean worlds provide fascinating opportunities for future ocean research. They allow us to test our understanding of processes we consider fundamental to Earth’s ocean and simultaneously provide motivation to explore our ocean further and develop new technologies to do so. In parallel, ocean worlds research offers opportunities for ocean scientists to provide meaningful contributions to novel investigations in the coming decades that will search for life beyond Earth. Key to the contributions that oceanographers can make to this field is that studies of all other ocean worlds remain extremely data limited. Here, we describe an approach based on ocean systems science in which theoretical modeling can be used, in concert with targeted laboratory experimentation and direct observations in Earth’s ocean, to predict what processes (including those essential to support life) might be occurring on other ocean worlds. In turn, such an approach would help identify new technologies that might be required for future space missions as well as appropriate analog studies that could be conducted on Earth to develop and validate such technologies. Our approach is both integrative and interdisciplinary and considers multiple domains, from processes active in the subseafloor to those associated with ocean-ice feedbacks.

Identification of QTLs for morphological traits influencing waterlogging tolerance in perennial ryegrass (Lolium perenne L.) - Allison Pearson; Noel O. I. Cogan; Rebecca C. Baillie; Melanie L. Hand; Champa K. Bandaranayake; Stacey Erb; Junping Wang; Gavin A. Kearney; Anthony R. Gendall; Kevin F. Smith; John W. Forster (Theoretical and Applied Genetics, 2011)

Identification of genetic factors influencing salt stress tolerance in white clover (Trifolium repens L.) by QTL analysis - Junping Wang; Michelle C. Drayton; Julie George; Noel O. I. Cogan; Rebecca C. Baillie; Melanie L. Hand; Gavin A. Kearney; Stacey Erb; Tania Wilkinson; Nathaniel R. Bannan; John W. Forster; Kevin F. Smith (Theoretical and Applied Genetics, 2010)

Identification of homologous, homoeologous and paralogous sequence variants in an outbreeding allopolyploid species based on comparison with progenitor taxa - Melanie L. Hand; Rebecca C. Ponting; Michelle C. Drayton; Kahlil A. Lawless; Noel O. I. Cogan; E. Charles Brummer; Timothy I. Sawbridge; German C. Spangenberg; Kevin F. Smith; John W. Forster (Molecular Genetics and Genomics, 2008)